Robust marker detection and high precision measurement for real‐time anatomical registration using Taguchi method. Issue 4 (7th April 2020) - Kaushik, Abhishek; Dwarakanath, T. A.; Bhutani, Gaurav
Abstract: Background: Accurate autonomous marker detection and measurement is essential for high precision anatomical registration. The measurement should be in real‐time, accurate, and robust to the varied conditions of the operation theatre. Methods: The purpose is to design and implement a robust real‐time algorithm to measure the coordinates of the point on the marker for robot‐based autonomous registration and surgery. The algorithm is built in two parts based on the recursive Taguchi method. The first part deals with the detection of markers. In the second part, the center of the marker is located, and the coordinates are measured by fitting the concentric ellipse. Results: Three case studies are presented where the algorithm is tested for extreme conditions of uneven lighting, distorted color, surface distortions, and significant random orientation of the marker. The robustness of the algorithm in successfully detecting and measuring in real‐time is presented. Conclusion: The algorithm is successfully implemented for real‐time detection and coordinate measurement of the markers.